Scientific Views and Views of Eastern Scholars on Physical Education and Sports - Sanjar, Muratov; Adilbek , Atajanov (International Journal of Human Computing Studies, 2022)
This article describes the views and opinions of Eastern scholars on physical education and sports. In particular, Alisher Navoi, Abu Ali ibn Sino, Amir Temur in their works expressed their views on the benefits of physical education and sports for human health